Affiliated Bank Performance and the Simultaneity of Financial Decision-Making - Graddy, Duane B.; Kyle, Reuben (Journal of Finance, 1980)
The remarkable growth of bank holding companies (BHCs) during the last decade has aroused a great deal of interest and controversy among academic economists and bank regulators. One of the important issues discussed has been the impact of holding company affiliation on the operating performance of the acquired banks. Subsequent empirical testing of the question has produced a wide array of results. Nevertheless, a recent survey of the literature by the staff of the Federal Reserve Board [18] concluded that while not entirely unambiguous, the findings are “relatively consistent and conclusive.” Such a sweeping generalization seems premature at best. In a recent issue of this Journal [4], we proposed an empirical model designed to test the interdependency between financial decision-making and bank performance. The purpose of this note is to examine the implications of that investigation for the BHC performance issue. The impact of affiliation on bank performance has been analyzed in several different ways; however, no study has considered the important theoretical and statistical implications of the simultaneity question.